2020
DOI: 10.1055/a-1334-4101
|View full text |Cite
|
Sign up to set email alerts
|

A Panoramic Review on Lepidium sativum L. Bioactives as Prospective Therapeutics

Abstract: Background Lepidium sativum (L. sativum), an annual herb belonging to family Brassicaceae is commonly known as Garden cress of Egyptian origin but now a day’s cultivated worldwide. The plant material and its constituents are used in various traditional and folk medicines for the treatment of various liver diseases and other ailments. Objective This review aims to gather comprehensive information on L. sativumʼs bioactive constituents, and itʼs antioxidant, hepato-protective and anticancer activity. Method Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The plant's anatomical parts, especially the seeds, exert their effects. Some research was performed on animal models to assess the healing properties of graden cress, and it was noticed that garden cress increased collagen deposition and tensile strength at the fracture sites and radiologically accelerated callus development in rabbits (Ahmad et al., 2021 ; Bin Abdullah Juma & Martin, 2011 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The plant's anatomical parts, especially the seeds, exert their effects. Some research was performed on animal models to assess the healing properties of graden cress, and it was noticed that garden cress increased collagen deposition and tensile strength at the fracture sites and radiologically accelerated callus development in rabbits (Ahmad et al., 2021 ; Bin Abdullah Juma & Martin, 2011 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Additionally, seeds had anti-diarrheal, anti-hypertensive, antidiabetic, antioxidant, diuretic, anti-carcinogenic properties 23,24 25 , anti-bacterial, cardio-protective 26 , anti-hypercholesterolemia 27,28 , anti-fungal, anti-osteoporotic and anti-inflammatory property 29 . Garden cress seed also have an ability to protect liver from toxicity and cancer 30 . Studies have too shown that L.…”
Section: Health Benefits Of Lepidium Sativummentioning
confidence: 99%
“…In addition to volatile oils, the leaves and seeds of this plant are rich in minerals, amino acids and fatty acids [ 37 , 39 ]. There is 33–54% carbohydrates in seeds, 25% protein, 14–24% lipids and 8% crude fibre in seeds [ 40 , 41 ]. LS has been reported for treatment of several disorders [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%